2020
DOI: 10.1088/1742-6596/1507/8/082041
|View full text |Cite
|
Sign up to set email alerts
|

Study of coupling thermal and mechanical effect on submerged nozzle in solid rocket motor

Abstract: The thermo-structural response of submerged nozzles is widely investigated in the design of modern rockets upon thermal loading and aerodynamic pressure. In this paper, by means of commercial finite element software with the subroutine of non-uniform pressure and non-uniform heat transfer coefficients, the simulation was performed to study the thermo-structural response of a submerged nozzle at the pressure 6MPa and stagnation temperature 3200K. By means of fluid software, the steady flow field with hot gas wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Gong et al [10] investigated the thermo-structural response of submerged nozzles. They found that the stresses increased clearly in case of combining both thermal and mechanical loadings much more than in the case of each one separately.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [10] investigated the thermo-structural response of submerged nozzles. They found that the stresses increased clearly in case of combining both thermal and mechanical loadings much more than in the case of each one separately.…”
Section: Introductionmentioning
confidence: 99%